The Effect of Bacillus altitudinis P-10 Combination Treatments on the Plant Growth and Seed Quality of Corn (Zea mays L) - Elfira, Yolanda; Kusmiyati, Florentina; Budiharjo, Anto (Bioma : Berkala Ilmiah Biologi, 2020)
Increasing production of Corn in recent years must be supported with the supply of good quality of seeds. Bacillus altitudinis P -10 is a plant growth promoting rhizobacteria that has biofetilizer and biopesticide activities. The aim of this research was to find out the effect of combination treatments of B. altitudinis P -10 on the growth pf the plant and seed quality of Corn (Zea mays L). The research design used was randomized group design with monofactor pattern of 4 combination treatments with 6 groups. The corn seed used was Lamuru varieties. The treatments consisted of D1 (manure), D2 (manure and B. altitudinis P-10), D3 (manure and chemical fertilizer), and D4 (manure, chemical fertilizer, and B. altitudinis P-10). The parameters observed included the height of the plant, the length of the root, the root dry matter, the crown dry matter, the total dry matter, the emergence time of male flower, the emergence time of female flower, the time of physiological ripening, the length of the cob, the diameter of the cob, the number of seeds per cob, the number of seeds per row per cob, the weight of 100 seeds, the production of the seed, the moisture content, the germination percentage, the purity and the impurity of seed. The results showed that the combination treatments of D4 gave the best parameter for the emergence time of flowers, the time of physiological ripening, the length of the cob, the diameter of the cob, the number of seeds per cob, the number of cobs per row, the weight of 100 seeds, and the production of the seed.